SRATEGI PENGEMBANGAN PARAWISATA DI KABUPATEN BENGKULU TENGAH - Sakti, Budiman; Novrin, Edward; Sutardi, Dodo (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
The tourism industry will become a lading sector driving the Indonesian economy, if it is managed, programmed and planned carefully and comprehensively. Central Bengkulu has many profitable opportunities that can be mined as a commodity if given the right strategic management as a tourist area. The aims of this research are, 1) To understand and analyze the tourism conditions in Central Bengkulu Regency using internal and external organizational debates in Central Bengkulu, 2) To understand and analyze the strategy for developing a tourist village in Central Bengkulu Regency in terms of external and internal environmental aspects. The research method used, descriptive research, using data collection methods, semi-structured interviews, structured interviews with the active participation of researchers. Information sources who became informants consisted of 10 people from the community and 5 people from the government in the tourism sector. The results of the research show that from the evaluation of the strategic environment, the strengths and weaknesses of the company's internal environment as well as the opportunities and risks of the company's external environment are identified. Improving the quality and quantity of human resources through a stable political situation obtains the highest score which means it has the highest strategic level.